In vitro leishmanicidal effect of Yangambin and Epi-yangambin lignans isolated from Ocotea fasciculata (Nees) Mez - Rebouças-Silva, Jéssica; Santos, Gabriel Farias; Filho, José Maria Barbosa; Berretta, Andresa A.; Marquele-Oliveira, Franciane; Borges, Valéria M. (Frontiers in Cellular and Infection Microbiology, 2023)
Yangambin and epi-yangambin are the main lignans found in Louro-de-Cheiro [Ocotea fasciculata (Nees) Mez], a tree native to the Atlantic forests of northeastern Brazil whose leaves and bark are widely used in folk medicine. The present study investigated the leishmanicidal and immunomodulatory effects of both lignans in in vitro models of infection by Leishmania amazonensis (La) or Leishmania braziliensis (Lb), both etiological agents of Cutaneous Leishmaniasis in Brazil. Bone marrow-derived mouse macrophages were infected with L. amazonensis or L. braziliensis and then treated for 48 h at varying concentrations of yangambin or epi-yangambin. Yangambin and epi-yangambin were found to reduce the intracellular viability of either Leishmania species in a concentration-dependent manner, with respective IC50 values of: 43.9 ± 5 and 22.6 ± 4.9 µM for La, compared to IC50 values of 76 ± 17 and 74.4 ± 9.8 µM for Lb. In this context, epi-yangambin proved more selective and effective against in vitro infection by L. amazonensis. However, both lignans were found to distinctly modulate the production of inflammatory mediators and other cytokines by macrophages infected by either of the Leishmania species evaluated. While yangambin increased the production of IL-10 by L. braziliensis-infected macrophages, both compounds were observed to lower the production of NO, PGE2, IL-6 and TNF-α in both Leishmania species. The present results serve to encourage the development of novel studies aimed at screening natural bioactive compounds with the hope of discovering new therapeutic options for the treatment of Cutaneous Leishmaniasis.